Retrospective study on prevalence of severe anemia in pregnant women and its outcome - R., Sudha; Madenor, Srushti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Anemia is one of the most common nutritional deficiency disorders affecting the pregnant women in the developing countries. Anemia during pregnancy is commonly associated with poor pregnancy outcome and can result in complications that threaten the life of both mother and fetus. The study aimed at analyse the maternal and perinatal outcome of pregnant women with severe anemia (Hb <7 gm%) in pregnancy. Aim and objective were to study the prevalence of anemia among pregnant women and to determine its association with maternal and fetal outcomes. Methods: A hospital-based retrospective study on the prevalence of anemia among the antenatal women for 6 months duration from February 2022 to July 2022 in department of obstetrics and gynecology Cheluvamba hospital, Mysore Medical College and Research Institute, Mysore. Results: Out of 4291 deliveries during the study period 76 (1.7%) patients were severely anaemic. There were 55 (72.3%) multigravida. Maternal complications were preterm labour 15 (16.8%), pre-eclampsia and eclampsia 10(13.1%), abortions 22 (28%). Neonatal outcome was analysed in terms of prematurity (16.8%), LBW (22.4%), NICU admission (17.9%), still birth (0.03%), neonatal deaths (0.05%). Conclusions: Severe anemia during pregnancy is associated with adverse maternal and perinatal outcome. It is one of the preventable indirect causes of maternal mortality. Education to adolescents, regular antenatal check-ups, early diagnosis and treatment, prevention of too late too early too frequent too many pregnancies. Educating the women regarding safe abortion services available thus avoiding unwanted pregnancies. Promotion of good nutrition practices thus reaching optimum haemoglobin before conception. Along with these active participation of health workers at grass-root level might help in bringing down the prevalence.